EXPLORING THE SOCIO-ECONOMIC IMPACT OF LIVESTOCK ON POVERTY ALLEVIATION: A CASE STUDY OF RURAL COMMUNITIES IN DISTRICT BUNER - Numan Khan; Muhammad Ashfaq; Muhammad Ibrahim (International Journal of Contemporary Issues in Social Sciences, 2024)
Livestock is a critical contributor to the rural economy of Pakistan, particularly in poverty alleviation. This study explores the socio-economic impact of livestock on poverty reduction in rural communities of District Buner, Khyber Pakhtunkhwa. Data was collected from 80 farmers across four tehsils through a structured questionnaire. A logit model was employed to analyze the relationship between livestock ownership and poverty alleviation. The findings reveal that income generated from livestock, other sources of income, household size, the number of animals owned, and the experience of the respondents significantly impact poverty levels. Livestock-related activities were found to boost household income, playing a pivotal role in reducing poverty among rural communities. The study concludes that livestock farming can be an effective tool for economic empowerment and poverty reduction in rural areas.